How Ibn Sinian Is Suhrawardi’s Theory of Knowledge? - saeed anvari; Mahdi Amin Razavi (حکمت اسرا, 2023)
In what follows, I will argue that despite apparent differences and the association with two different schools of thought, the epistemology of Suhrawardı is essentially that of Ibn, and even Suhrawardı’s theory of ‘‘knowledge by presence’’, which is considered to be uniquely his, is at least inspired by Ibn Sına. I will argue that Ibn Sına’s peripatetic orientation and Suhrawardı’s ishraqı perspective have both maintained and adhered to the same epistemological framework while the philosophical language in which their respective epistemologies are discussed is different. Of particular interest in our investigation is to show that both masters have adhered to a hierarchy of knowledge as follows: 1. Knowledge by definition; 2. Knowledge by sense perception; 3. Knowledge through a priori concepts; 4. Knowledge by presence; 5. Knowledge through direct experience: mysticism. The fact is that mysticism, in both its philosophical and its practical senses, is a component of the philosophical edifice of Ibn Sına and Suhrawardı, and the type of knowledge that is attained through mysticism is regarded by both philosophers to be the purest form of knowledge, one that is clear, distinct, unmediated, and direct. The knowledge attained through mysticism for Ibn Sına and Suhrawardı is not only informative but also transformative, a quality that both philosophers allude to in very clear and specific language, leaving no doubt that mysticism is an inseparable and integral part of the philosophical schools of both Ibn Sına and Suhrawardı.